2021
DOI: 10.1007/s40868-021-00104-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of micro bubble drag reduction effect for container ships

Abstract: In the course of the most recent thirty years reduction of ship resistance and saving fuel consumption to accomplish higher speed with reduction of pollutants has been the significant subject for researchers. Micro bubble drag reduction technique is the one of the most interesting thoughts in this field owing to its great advantages, such as considerable potential drag reduction, easy operations, environmental friendliness and low costs. In this study a 3-D numerical investigation into frictional drag reductio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This phenomenon is thought to involve air trapped under feathers that is released to lower drag during the jump 6 . Micro‐bubbles, which attach to and are emitted from the hydrophobic feathers, 7 indicate the free‐shear boundary condition on the body, thereby reducing drag 8–14 . Additionally, plunge‐diving birds have been observed to release bubbles from the air trapped in their underlying feathers (see Figure 1A) as they descend while plunging and rapidly swimming 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is thought to involve air trapped under feathers that is released to lower drag during the jump 6 . Micro‐bubbles, which attach to and are emitted from the hydrophobic feathers, 7 indicate the free‐shear boundary condition on the body, thereby reducing drag 8–14 . Additionally, plunge‐diving birds have been observed to release bubbles from the air trapped in their underlying feathers (see Figure 1A) as they descend while plunging and rapidly swimming 3 .…”
Section: Introductionmentioning
confidence: 99%
“…6 Micro-bubbles, which attach to and are emitted from the hydrophobic feathers, 7 indicate the free-shear boundary condition on the body, thereby reducing drag. [8][9][10][11][12][13][14] Additionally, plunge-diving birds have been observed to release bubbles from the air trapped in their underlying feathers (see Figure 1A) as they descend while plunging and rapidly swimming. 3 Despite some studies demonstrating a relationship between drag and the feathers of surface-diving birds, 15,16 the effect of the bubble release of plungediving birds on drag remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, bubbles adhering to the electrode would hinder the contact between the electrode and the electrolyte, thereby reducing the efficiency of the electrochemical reaction. Bubbles can also adhere to underwater cameras or diving goggles, which results in poor visibility . On the other hand, attaching bubbles to the surface of the underwater vehicle can significantly reduce the resistance between water and the vehicle. It is also found that attaching bubbles can enhance the sealing performance of biological suckers , and artificial suckers . Therefore, the reliable manipulation of bubbles on the substrate is of vital importance.…”
Section: Introductionmentioning
confidence: 99%
“…One of these methods relies on the use of baffles of various heights in the turbulent flow zone to suppress turbulent eddies [1]. Other methods include oily materials or bubble layers to decrease skin friction [2]. However, adding minute amount of chemical agents to fluids delivered through pipes is the most effective method of reducing drag [3].…”
Section: Introductionmentioning
confidence: 99%